Sperm parameter variability in Donggala bulls: An objective-based analysis of frozen semen quality - Mangun, Mardiah; Duma, Yulius; Baharun, Abdullah; Handarini, Ristika; Said, Syahruddin; Putra, Widya Pintaka Bayu; Kaiin, Ekayanti Mulyawati; Pardede, Berlin Pandapotan; Maulana, Tulus (Journal of Advanced Veterinary and Animal Research, 2025)
Objective: This study aimed to evaluate the properties of fresh and frozen semen from Donggala bulls at the Regional Technical Service Unit of Livestock Breeding in Sidera District, Central Sulawesi. Materials and Methods: Fresh semen from six selected Donggala bulls was collected using an artificial vagina during the same collection period and weather conditions once per week for four consecutive weeks. Subsequently, the semen was assessed for sperm quality, including volume, pH, mass movement, motility, and concentration. Frozen semen produced from the ejaculation of each bull was used for further analysis (motility, viability, membrane integrity, morphology, and sperm acrosomal status). Results: Fresh semen parameters, including volume, mass movement, sperm motility, and concentration, differed significantly (p < 0.05) among individual Donggala bulls. In contrast, analysis of frozen-thawed semen showed no significant variations among individual bulls regarding sperm motility, abnormality, or membrane integrity, except for sperm viability and acrosomal integrity. Bulls with ID No. 102 and Bull 104 had significantly lower sperm viability (p < 0.05) than Bull No. 103. There was also a significant difference (p < 0.05) in sperm acrosome integrity between bulls. The results of analysis by computer-assisted sperm analysis (CASA) showed significant differences (p < 0.05). In the kinematic parameters of Donggala bull sperm, particularly in velocity straight line, distance straight line, beat cross frequency, and amplitude of lateral head displacement. In contrast, mitochondrial membrane potential (MMP) did not significantly differ (p > 0.05) among bulls. Conclusion: All Donggala bulls showed adequate fertilization ability and good MMP. Flow cytometry and CASA integration provide a rapid and unbiased approach to sperm quality assessment. J. Adv. Vet. Anim. Res., 12(3): 832–839, September 2025 http://doi.org/10.5455/javar.2025.l945